Participation in the pancyprian theatrical school contest of French plays with an extract of the novel Le Petit Prince of Antoine de Saint-Exupéry - Georgiadou, Olga (My University, 2026)
Participation in the pancyprian theatrical school contest of French plays with an extract of the novel Le Petit Prince of Antoine de Saint-Exupéry